1998
DOI: 10.1200/jco.1998.16.7.2401
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a practical prognostic index for patients with metastatic breast cancer.

Abstract: ADJCT, DLNs, HEP, LDH, and DFI were important prognostic factors for MBC patients. The prognostic index readily enables MBC patients to be stratified into three risk groups and is worth considering for future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 0 publications
11
78
1
2
Order By: Relevance
“…In particular, none of the tumour TF-negative patients had liver metastasis, although this result is preliminary. Liver metastasis is well-known to provide a poor prognosis in breast cancer patients (Yamamoto et al, 1998). Taken together, although no difference in prognosis was observed for disease-free survival, the difference in metastatic sites between tumour TF-positive and -negative patients might result in the significant difference in prognosis for overall survival.…”
Section: mentioning
confidence: 81%
“…In particular, none of the tumour TF-negative patients had liver metastasis, although this result is preliminary. Liver metastasis is well-known to provide a poor prognosis in breast cancer patients (Yamamoto et al, 1998). Taken together, although no difference in prognosis was observed for disease-free survival, the difference in metastatic sites between tumour TF-positive and -negative patients might result in the significant difference in prognosis for overall survival.…”
Section: mentioning
confidence: 81%
“…-For metastases to other organs, spread to the liver is known to associated with poor prognosis after [40,43], similarly for two metastatic foci [44][45]. Fro m CT3, liver involvement does not appear to affect survival as it was not affected at mult ivariate analysis, unlike mu ltiple metastatic foci.…”
Section: Discussionmentioning
confidence: 96%
“…-A long interval, greater than 2 years, between the diagnosis of breast cancer and metastatic relapse also favors good prognosis after CT1 [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Construction and validation of a practical prognostic index for patients with metastatic breast cancer was reported by Yamamoto and colleagues (40). Multivariate analyses of data from 233 patients with metastatic breast cancer showed that LDH was among 5 factors prognostic for survival.…”
Section: Discussionmentioning
confidence: 99%